0
$\begingroup$

I am struggling with the following problem and am looking for some guidance.

Find the solution to the 1-D heat equation given the following conditions:

A sphere with radius 0 < r < a with initial temperature f[r] and surface temperature Phi[t].z The boundary conditions for u[r, t] are:

u[0, t] == 0
u[a, t] == a Phi[t]

The initial condition is:

u[r, 0] == r f[r]
heqn = D[u[r, t], t] == k*D[u[r, t], {r, 2}];
bc1 = u[0, t] == 0;
bc2 = u[a, t] == a*[Phi][t];
ic = u[r, 0] == r*f[r]; 
sol = DSolve[{heqn, ic, bc1, bc2}, u[r, t], {r, t}];

Any suggestions?

$\endgroup$
  • $\begingroup$ Mathematica DSolve can't solve heat PDE in 1D with boundary conditions that is time dependent. ps. why do you write [Phi][t] instead of Phi[t] ? Or is this a copy/paste thing? $\endgroup$ – Nasser Apr 16 at 2:43
  • $\begingroup$ Sorry about that. It was a copy and paste error. Is there another function you would suggest? $\endgroup$ – Travis Apr 16 at 3:20
  • $\begingroup$ I suppose a "by hand" solution would be helpful. If you're willing, that is. It would be appreciated. $\endgroup$ – Travis Apr 16 at 3:37
4
$\begingroup$

I suppose a "by hand" solution would be helpful. If you're willing, that is. It would be appreciated

Ok, here it is

Solve \begin{equation} u_{t}=ku_{rr}\qquad t>0,0<r<a\tag{1} \end{equation} With boundary conditions \begin{align*} u\left( 0,t\right) & =0\\ u\left( a,t\right) & =a\phi\left( t\right) \end{align*}

And initial conditions $$ u\left( r,0\right) =rf\left( r\right) $$ Since the boundary conditions are not homogeneous, the first step is to convert them to homogeneous. This is done using a reference function which needs to only satisfy the boundary conditions. This reference function can be seen to be $v\left( r,t\right) =r\phi\left( t\right) $. Now we write $$ u\left( r,t\right) =w\left( r,t\right) +v\left( r,t\right) $$ Where $w\left( r,t\right) $ satisfies the PDE but with homogeneous B.C. Substituting the above into (1) gives \begin{align} w_{t}\left( r,t\right) +r\phi^{\prime}\left( t\right) & =kw_{rr} \nonumber\\ w_{t}\left( r,t\right) & =kw_{rr}-r\phi^{\prime}\left( t\right) \tag{2} \end{align} With boundary conditions \begin{align*} w\left( 0,t\right) & =0\\ w\left( a,t\right) & =0 \end{align*} The solution to the homogeneous PDE $w_{t}\left( r,t\right) =kw_{rr}$ with the above boundary conditions is easily found and known. The eigenvalues are $\lambda_{n}=\left( \frac{n\pi}{a}\right) ^{2},n=1,2,\cdots$ and eigenfunctions $\Phi_{n}\left( r\right) =\sin\left( \sqrt{\lambda_{n} }r\right) $. Let the solution to (2), using eigenfunction expansion be \begin{equation} w\left( r,t\right) =\sum_{n=1}^{\infty}C_{n}\left( t\right) \Phi _{n}\left( r\right) \tag{2A} \end{equation} Substituting the above back into (2) gives \begin{equation} \sum_{n=1}^{\infty}C_{n}^{\prime}\left( t\right) \Phi_{n}\left( r\right) =k\sum_{n=1}^{\infty}C_{n}\left( t\right) \Phi_{n}^{\prime\prime}\left( r\right) -\sum_{n=1}^{\infty}q_{n}\left( t\right) \Phi_{n}\left( r\right) \tag{3} \end{equation} Where $q_{n}\left( t\right) $ are the Fourier coefficients of $r\phi ^{\prime}\left( t\right) $ which are found by $$ r\phi^{\prime}\left( t\right) =\sum_{n=1}^{\infty}q_{n}\left( t\right) \Phi_{n}\left( r\right) $$ Applying orthogonality using $\Phi_{n}\left( r\right) $ gives \begin{align*} \int_{0}^{a}r\phi^{\prime}\left( t\right) \Phi_{m}\left( r\right) dr & =\int_{0}^{a}\sum_{n=1}^{\infty}q_{n}\left( t\right) \Phi_{n}\left( r\right) \Phi_{m}\left( r\right) dr\\ & =\sum_{n=1}^{\infty}q_{n}\left( t\right) \int_{0}^{r}\Phi_{n}\left( r\right) \Phi_{m}\left( r\right) dr \end{align*} But $\int_{0}^{a}\Phi_{n}\left( r\right) \Phi_{m}\left( r\right) dr=\int_{0}^{a}\sin\left( \frac{n\pi}{a}r\right) \sin\left( \frac{m\pi} {a}r\right) dr=\frac{a}{2}$ for $n=m$ only, and the above becomes $$ \frac{2}{a}\int_{0}^{a}r\phi^{\prime}\left( t\right) \Phi_{m}\left( s\right) dr=q_{m}\left( t\right) $$ Substituting the above back into (3) gives $$ \sum_{n=1}^{\infty}C_{n}^{\prime}\left( t\right) \Phi_{n}\left( r\right) =k\sum_{n=1}^{\infty}C_{n}\left( t\right) \Phi_{n}^{\prime\prime}\left( r\right) -\sum_{n=1}^{\infty}\left( \frac{2}{a}\int_{0}^{a}r\phi^{\prime }\left( t\right) \Phi_{m}\left( r\right) dr\right) \Phi_{n}\left( r\right) $$ But $\Phi_{n}^{\prime\prime}\left( r\right) =-\lambda_{n}\Phi_{n}\left( r\right) $ and above simplifies to \begin{align*} \sum_{n=1}^{\infty}C_{n}^{\prime}\left( t\right) \Phi_{n}\left( r\right) +k\sum_{n=1}^{\infty}C_{n}\left( t\right) \lambda_{n}\Phi_{n}\left( r\right) & =-\sum_{n=1}^{\infty}\left( \frac{2}{a}\int_{0}^{a} r\phi^{\prime}\left( t\right) \Phi_{m}\left( r\right) dr\right) \Phi _{n}\left( r\right) \\ C_{n}^{\prime}\left( t\right) +kC_{n}\left( t\right) \lambda_{n} & =-\frac{2}{a}\int_{0}^{a}r\phi^{\prime}\left( t\right) \Phi_{m}\left( r\right) dr\\ & =-\frac{2}{a}\phi^{\prime}\left( t\right) \int_{0}^{a}r\sin\left( \frac{n\pi}{a}r\right) dr\\ & =-\frac{2}{a}\phi^{\prime}\left( t\right) \frac{\left( -1\right) ^{n+1}a^{2}}{n\pi}\\ & =-2a\phi^{\prime}\left( t\right) \frac{\left( -1\right) ^{n+1}}{n\pi} \end{align*} This is first order ODE in $C\left( t\right) $. The solution is $$ C_{n}\left( t\right) =e^{-k\lambda_{n}t}C_{n}\left( 0\right) +2ae^{-k\lambda_{n}t}\frac{\left( -1\right) ^{n+1}}{n\pi}\int_{0}^{t} \phi^{\prime}\left( \tau\right) e^{k\lambda_{n}\tau}d\tau $$ From (2A) $$ w\left( r,t\right) =\sum_{n=1}^{\infty}\left( e^{-k\lambda_{n}t} C_{n}\left( 0\right) +2ae^{-k\lambda_{n}t}\frac{\left( -1\right) ^{n+1} }{n\pi}\int_{0}^{t}\phi^{\prime}\left( \tau\right) e^{k\lambda_{n}\tau} d\tau\right) \sin\left( \frac{n\pi}{a}r\right) $$ Hence \begin{align} u\left( r,t\right) & =w\left( r,t\right) +v\left( r,t\right) \nonumber\\ & =\sum_{n=1}^{\infty}\left( e^{-k\lambda_{n}t}C_{n}\left( 0\right) +2ae^{-k\lambda_{n}t}\frac{\left( -1\right) ^{n+1}}{n\pi}\int_{0}^{t} \phi^{\prime}\left( \tau\right) e^{k\lambda_{n}\tau}d\tau\right) \sin\left( \frac{n\pi}{a}r\right) +r\phi\left( t\right) \tag{4} \end{align} At $t=0$ the above becomes \begin{align*} rf\left( r\right) & =\sum_{n=1}^{\infty}C_{n}\left( 0\right) \sin\left( \frac{n\pi}{a}r\right) +r\phi\left( 0\right) \\ \sum_{n=1}^{\infty}C_{n}\left( 0\right) \sin\left( \frac{n\pi}{a}r\right) & =r\left( f\left( r\right) -\phi\left( 0\right) \right) \end{align*} Hence $C_{n}\left( 0\right) $ is the Fourier sine coefficients of $\ r\left( f\left( r\right) -\phi\left( 0\right) \right) $ \begin{align*} \frac{a}{2}C_{n}\left( 0\right) & =\int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr\\ C_{n}\left( 0\right) & =\frac{2}{a}\int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr \end{align*}

Substituting this into (4) gives the final solution as \begin{align*} u\left( r,t\right) & =r\phi\left( t\right) +\sum_{n=1}^{\infty}\left( e^{-k\lambda_{n}t}\left( \frac{2}{a}\int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr\right) +2ae^{-k\lambda_{n}t}\frac{\left( -1\right) ^{n+1}}{n\pi}\int_{0}^{t} \phi^{\prime}\left( \tau\right) e^{k\lambda_{n}\tau}d\tau\right) \sin\left( \frac{n\pi}{a}r\right) \\ & =r\phi\left( t\right) +\sum_{n=1}^{\infty}\left( e^{-k\lambda_{n} t}\left( \frac{2}{a}\int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr\right) +2a\frac{\left( -1\right) ^{n+1}}{n\pi}\int_{0}^{t}\phi^{\prime}\left( \tau\right) e^{-k\lambda_{n}\left( t-\tau\right) }d\tau\right) \sin\left( \frac{n\pi}{a}r\right) \\ & =r\phi\left( t\right) +\sum_{n=1}^{\infty}e^{-k\lambda_{n}t}\left( \frac{2}{a}\int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr\right) \sin\left( \frac {n\pi}{a}r\right) +\sum_{n=1}^{\infty}2a\frac{\left( -1\right) ^{n+1}} {n\pi}\int_{0}^{t}\phi^{\prime}\left( \tau\right) e^{-k\lambda_{n}\left( t-\tau\right) }d\tau\sin\left( \frac{n\pi}{a}r\right) \end{align*}

Or

\begin{align*} u\left( r,t\right) & =r\phi\left( t\right) \\ & +\frac{2}{a}\sum_{n=1}^{\infty}e^{-k\lambda_{n}t}\sin\left( \frac{n\pi} {a}r\right) \left( \int_{0}^{a}r\left( f\left( r\right) -\phi\left( 0\right) \right) \sin\left( \frac{n\pi}{a}r\right) dr\right) \\ & +\frac{2a}{\pi}\sum_{n=1}^{\infty}\frac{\left( -1\right) ^{n+1}}{n} \sin\left( \frac{n\pi}{a}r\right) \int_{0}^{t}\phi^{\prime}\left( \tau\right) e^{-k\lambda_{n}\left( t-\tau\right) }d\tau \end{align*}

Where $\lambda_{n}=\left( \frac{n\pi}{a}\right) ^{2}$.

I can use NDSolve to verify the above solution and comparing them. But I do not have values for your a,f[r],phi[t] to do that. If you have these, I could try to do that.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.